(untitled) (Human Factors in Design, 2022)
Daily activities need ergonomic analyses, especially when it comes to environments occupied by users with visual impairments. Thus, the aim of this article was to develop an Ergonomic Work Analysis (EWA) in a home kitchen of a user with visual impairment. For this, a methodology based on the steps of EWA was used. The results showed that: the activities performed demanded greater use of the cognitive aspect; the arrangement of equipment proved to be problematic and; the main equipment was incompatible with the user’s anthropometric conditions. It was concluded that ergonomic tools are needed that absorb aspects such as spatial orientation and mobility.